Ikhlas Tinjauan Normatif dan Historis - Ritonga, Ahmad Husein (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2007)
The word ikhlas, which is sometimes interpreted mystically, has the meaning as an attitude towards something without any interest. This study is to discuss the exact concept of ikhlas in the holy Koran. Ikhlas is the process of purification of aqidah (ftrth), ibadah (religious service) and muamalah (religious social interaction) bssed on the norms which has been determined by Allah and his Prophet. The analysis of Koranic themes and verses should be put according to the conclition of human kind objectively and still in the context of the given verses.